Aquifer characterization and performance of tubewell using GIS - Kamal, Md. Rowshon; Khan, L. R.; Kwok, Chee Yan; Lee, Teang Shui (Universiti Putra Malaysia, 1999)
The existing well logs at different locations have been analyzed to predict the characterization of aquifer and groundwater reserve within the BAU area. Digitized Map features of Sub-surface lithology and Fence diagram explains and interprets the nature of lithologic formation of aquifer and visualization of information. Different methods were used to determine the hydraulic characterization of the aquifer using pumping test data of the selected DTW 0.056 m3/s. A computer based optimization technique was used to determine the drawdown parameters. The efficiency of DTW was also been tested using computed drawdown. Geographical Information System (GIS) has potential in applications that will efficient interpretation and visualization of the aquifer characteristics and simulated results.